Assessment of health-related quality of life after hepatocellular carcinoma management (radiofrequency ablation or transarterial chemoembolization): a pilot Egyptian study. Issue 3 (July 2017) - Hamdy, Hassan; Barakat, Eman M.; El-Folly, Runia F.; Ahmed, Amr M.; El-Hariri, Hazem; Abdelghany, Reda S.; El-Fouly, Nevien F.
Abstract : Introduction: Among patients with hepatocellular carcinoma (HCC), as the major bad progress and complication of chronic liver disease (CLDs), impairment in health-related quality of life (HRQoL) has been reported. For this purpose, the relationship between subjective HRQoL scores and HCC stage according to Barcelona Clinic Liver Cancer staging and a therapeutic algorithm system should be analyzed further. Aim: This study aimed to assess the effect of HCC and different locoregional HCC therapy [radiofrequency ablation (RFA) or transarterial chemoembolization (TACE)] on the HRQoL. Patients and methods: Eighty HCC patients with CLD, 58 (72.5%) men and 22 (27.5%) women, mean age 51.8±6.2 years, were categorized into two groups. Group I included 40 HCC patients treated with RFA and group II included 40 HCC patients treated with TACE. The control Group included 40 CLD patients without HCC. HCC was managed according to the Barcelona Clinic Liver Cancer algorithm. The Short Form-36 questionnaires were filled in before and 1 month after the intervention. Results: It was found that HRQoL in the control group was significantly better than in those who underwent TACE, but almost equal to those who underwent RFA. In group I, all parameters of HRQoL were statistically improved after RFA ( P <0.05). Also, HRQoL was statistically better in those with a complete response (70% in group I and 55% in group II) than in those with an incomplete response (30% in group I and 40% in group II) after RFA ( P <0.05). Conclusion: Improvements in overall HRQoL in HCC patients were achieved after the intervention, especially after RFA, and in those with a complete response after the intervention than those with an incomplete response.